Media Puzzle Dalam Penguasaan Kosakata Bahasa Jerman - Ratih Salwa; Misnawaty Usman; Nurming Saleh (Phonologie : Journal of Language and Literature, 2021)
Abstract. This research was conducted to obtain data and information on the effectiveness of puzzle media in mastering German vocabulary for XI grade students of SMA Negeri 8 Makassar. The type of this research is quasi-experimental and the data is obtained through a vocabulary mastery test and the data is analyzed by t-test. The population of this research is the XI grade students of SMA Negeri 8 Makassar which consists of six classes and 180 students. The sample used was a random sample (Randam Sampling) consisting of 60 students, namely 30 students of XI Mipa2 as the experimental class and 30 students of XI Mipa3 as the control class. The results of data analysis obtained through tcount = 5.11> ttable = 2.002 at a significance level of 0.05. The results of this study indicate that the puzzle media is effective in mastering the German vocabulary of class XI students of SMA Negeri 8 Makassar.